Assessment of Vermicompost and Seaweed Extract Efficiency in Enhancing Maize Hybrid Tolerance to Water Stress - Al-Edelbi, Reem; AL-Boush, Esraa (Jordan Journal of Agricultural Sciences, 2025)
The research was conducted at Abu Garash Farm, Faculty of Agriculture, Damascus University, during the 2023 agricultural season. The aim was to study the effect of vermicompost fertilizer and seaweed extract on enhancing the tolerance of four maize hybrids to water stress before reaching the flowering stage, approximately 17 days prior. The experiment was designed using a randomized complete block design (RCBD) with three replications. The results indicated significant differences among the fertilizer treatments, hybrids, and the interaction between hybrids and fertilizer treatments for all the studied traits. The hybrid (IL-200-14 × IL-90-14) exhibited superiority in leaf area (5396 cm2), number of grains per cob (326.1 grain.cob-1), and grain yield per plant (56.21 g. plant-1). Conversely, the vermicompost fertilizer treatment showed superiority in plant height (157.53 cm), leaf area (4865 cm2), number of grains per cob (359.8 grain.cob-1), 100-grain weight (20.28 g), and grain yield per plant (73.5 g. plant-1). These results suggest the positive impact of vermicompost fertilizer in enhancing the crop’s ability to tolerate drought stress and produce a good grain yield.